Modern weapons and military equipment for issue 4-2016 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Long rangers: SLCMs still add reach and strategic impact, Piranha 5: militaries remain hooked on proven platform, Will we ever build more F-22?, Russia's Next Super Submarine Is Almost Ready for War, Joint effort, New BMP-1 upgrade developed in Ukraine, China expands family of wheeled fire-support platforms, Progresse: French armour programmes move ahead.